Legal Clarity for Sharia Lodging Businesses through Sharia Certification - Rasmuddin, Rasmuddin; Umar, Wahyudi; Sudirman, Sudirman; Lambooy, Tineke (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2024)
The development of the Sharia business in Indonesia has become the most potential business not only in Islamic banking but also the non-Islamic bank financial industries, such as Islamic insurance, Islamic pension funds, Islamic finance companies, Islamic bonds (sukuk), Islamic mutual funds, and even Islamic lodging. This phenomenon makes the Sharia